Agrivoltaics: The Environmental Impacts of Combining Food Crop Cultivation and Solar Energy Generation - Moritz Wagner; Jan Lask; Andreas Kiesel; Iris Lewandowski; Axel Weselek; Petra Högy; Max Trommsdorff; Marc-André Schnaiker; Andrea Bauerle (Agronomy, 2023)
The demand for food and renewable energy is increasing significantly, whereas the availability of land for agricultural use is declining. Agrivoltaic systems (AVS), which combine agricultural production with solar energy generation on the same area, are a promising opportunity with the potential to satisfy this demand while avoiding land-use conflicts. In the current study, a Consequential Life-Cycle Assessment (CLCA) was conducted to holistically assess the environmental consequences arising from a shift from single-use agriculture to AVS in Germany. The results of the study show that the environmental consequences of the installation of overhead AVS on agricultural land are positive and reduce the impacts in 15 of the 16 analysed impact categories especially for climate change, eutrophication and fossil resource use, as well as in the single score assessment, mainly due to the substitution of the marginal energy mix. It was demonstrated that, under certain conditions, AVS can contribute to the extension of renewable energy production resources without reducing food production resources. These include maintaining the agricultural yields underneath the photovoltaic (PV) modules, seeking synergies between solar energy generation and crop production and minimising the loss of good agricultural land.